Les constructions siamoises en français et dans cinq autres langues européennes. Étude sur la comparative corrélative - Stage, Lilian (HERMES - Journal of Language and Communication in Business, 2009)
This article discusses the comparative correlative constructions in French and ﬁve other European languages. A comparative correlative construction is a binary structure whose two parts are conjoined as Siamese twins (to use the ﬁne metaphor invented by Savelli, a French linguist). The most striking feature of this construction is the fronting of the comparatives in two clauses which are interdependent and inseparable, though at ﬁrst glance no clear relation can be seen, neither in French nor in English. It is hoped that this study of six European languages will contribute to an elucidation of the structuring of the two clauses and the relation between the two parts as well as the meaning they convey.